Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn413
|View full text |Cite
|
Sign up to set email alerts
|

Psychology and Neuroscience of Person Perception

Abstract: Understanding other people is an important and consequential task, and thus it is not surprising that the perceptual system is attuned to extract relevant information (e.g., social categories, identity, traits, and intentions) available in the faces, bodies, and voices of other people. As a result, social information is quickly inferred from even a brief glimpse of another's face, although this process can be prone to systematic biases. Recent interdisciplinary developments spanning across social psychology, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…In Studies 20–23, we tested the generalizability of the discrepancy findings to other social groups (old and young people) and to non-American population (Israelis). We chose the groups old and young people because, like race, age is processed relatively quickly and is commonly used to categorize individuals to groups (Brooks & Freeman, 2018). We tested whether the preference measured with an indirect measure would be less favorable of famous old people (compared with famous young people) than the preference measured with a direct measure.…”
Section: Studies 20–23: Generalization To Other Participant Populatio...mentioning
confidence: 99%
“…In Studies 20–23, we tested the generalizability of the discrepancy findings to other social groups (old and young people) and to non-American population (Israelis). We chose the groups old and young people because, like race, age is processed relatively quickly and is commonly used to categorize individuals to groups (Brooks & Freeman, 2018). We tested whether the preference measured with an indirect measure would be less favorable of famous old people (compared with famous young people) than the preference measured with a direct measure.…”
Section: Studies 20–23: Generalization To Other Participant Populatio...mentioning
confidence: 99%
“…Face "averageness," on the other hand, has been shown to increase judgments of trustworthiness (Sofer et al, 2015). Brooks and Freeman (2018) also review previous research on vocal cues for mental models of others, noting that very short voice samples can lead to accurate predictions of body size, affect, age, gender, and race. Listeners also feel confident in making judgments about trustworthiness based on voice, whether or not they are correct.…”
Section: Behavioral Markers Of Mental Models Within the Telecommunications Contextmentioning
confidence: 97%
“…In the context of both face-to-face and computer-mediated communication, mental models will be informed by the person's social and cultural context (Mantovani, 1996; for review, see Lee & Malcein, 2020). The unconscious categorization of others into social categories may also contribute to the formation of mental models based on a persons' previous experience with other demographically similar individuals or based on an accurate estimation of personality traits from brief video clips (i.e., person perception; for review, see Brooks & Freeman, 2018). Often only a few seconds in length, video clips showing "thin slices" of behavior offer cues such as facial expressions, voice cues, and body pose that influence categorization (Weisbuch & Ambady, 2011).…”
Section: Mental Modelsmentioning
confidence: 99%
“…Perceiving people in images differs from perceiving people in real-life situations. However, several studies have found people use similar strategies (e.g., categorization) and pay attention to similar features when perceiving people in images and in real-life encounters (Brooks and Freeman 2018;Oosterhof and Todorov 2008). In addition, in both situations, people use their knowledge and experience of social life when categorizing the people (Demarrais and Robb 2013;Yang 2015).…”
Section: Participants and Datamentioning
confidence: 99%